STRATEGI PEMASARAN JASA PADA HOTEL ROSALI SITUBONDO - Fizaldi, Bayu; Ihsan, Anas Malik Fauzan; Ibad, Ersatul; Pratama, Rico Arif; Aziz, Muhamad Zitkul (Fakultas Ekonomi dan Bisnis, 2022)
The hotel industry is a service industry that offers room service, food and beverage providers and other services to the general public which are managed commercially. The research entitled